Findbuch des Bestandes Abt. 68 Oberste Zoll- und Kommerzbehörden in den Herzogtümern und in Kopenhagen bis 1867 - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2019)
The administration of customs and commercial affairs in Denmark and the Duchies of Schleswig, Holstein and (since 1816) Lauenburg has been the responsibility of a number of authorities at the central administrative level: Chamber of Rents in Copenhagen (1660 to 1848), General Country Economics and Commerce College ("General-Landes-Ökonomie- und Kommerzkollegium") (from 1735), West Indo-Guinean Chamber of Rents and General Customs (from 1760), Directorate of Upper Tax in Copenhagen in 1762 (from 1778 Directorate of State Balance and Upper Tax), 1782), unification of the General Country Economics and Commerce College and the West Indo-Guinean Retirement and General Customs Chamber ("Rente- und Generalzollkammer") to the Generalzollkammer- und Kommerzkollegium (1816). With the introduction of the Ministerial Constitution in Denmark in 1848, the activities of the General Chamber of Customs and Commerce ceased. Its responsibility for customs was transferred to the newly established Ministry of Finance. Initially, however, this administrative restructuring only affected the Kingdom of Denmark. With the outbreak of the survey in March 1848, the duchies had their own customs offices under the respective survey authorities. After the end of the survey in 1851, the duchies in Denmark were also given their own ministries in accordance with the reform. However, their powers in customs were transferred to the Ministry of Finance as early as 1852 and finally changed to the newly established Ministry for the Common Internal Affairs of the Monarchy in 1856, only to be transferred back to the Ministry of Finance after its abolition in 1858. The latter, in turn, had the customs system administered by the Directorate General of Customs, set up in 1855 and subordinate to the Ministry. The present register of findings lists only a very small part of the tradition of the supreme customs and commercial authorities responsible for the Kingdom of Denmark and the duchies. The main body of the records of the authorities listed in the finding bookcan be found in the Danish Imperial Archives in Copenhagen